Enhancing junior high school teachers' innovation through independent training andlearning communities - Ony Edyawaty; Anna Fitrotunnisa; Rhini Fatmasari (Inovasi Kurikulum, 2025)
The lack of teacher innovation due to limited need-based training and insufficient collaboration necessitates efforts to enhance innovation in junior high school teaching. This study examines the relationship between Independent Training and Learning Communities and their combined contribution to Teacher Innovation in Subang Regency, West Java, public junior high schools. This research employs a quantitative approach with correlation regression analysis. The sample consists of 296 civil servant teachers, selected purposely from a population of 1,132 teachers across 38 public junior high schools. Additionally, the results of questionnaires for 38 school principals were conducted to provide supporting data. The findings indicate that teachers actively participating in Independent Training tend to demonstrate greater innovation in their teaching practices. Learning Communities also foster innovation by facilitating discussions and exchanging best practices. The two variables exhibit a reinforcing relationship, where their simultaneous implementation results in a more substantial impact on teacher innovation. This study recommends optimizing Independent Training and Learning Communities, alongside strengthening the role of school principals in supervision, to promote sustainable innovation in teaching practices.   Abstrak Minimnya inovasi guru akibat terbatasnya pelatihan berbasis kebutuhan dan kurangnya kolaborasi menuntut peningkatan daya inovasi guru guna mendukung kualitas pembelajaran di SMP. Penelitian ini menganalisis hubungan antara pelatihan mandiri dan komunitas belajar terhadap daya inovasi guru di SMP Negeri Kabupaten Subang, serta kontribusi keduanya secara bersama. Penelitian ini menggunakan metode kuantitatif dengan analisis regresi korelasi. Sampel terdiri dari 296 guru ASN yang dipilih secara purposive dari populasi 1.132 guru di 38 SMP Negeri. Selain itu, hasil kuesioner terhadap 38 kepala sekolah digunakan sebagai data pendukung. Hasil penelitian menunjukkan bahwa guru yang aktif dalam Pelatihan Mandiri lebih inovatif dalam pembelajaran. Komunitas Belajar juga berperan dalam mendorong inovasi melalui diskusi dan berbagi praktik baik. Kedua variabel ini memiliki keterkaitan yang saling menguatkan, di mana penerapan secara bersamaan berdampak lebih signifikan terhadap daya inovasi guru. Penelitian merekomendasikan optimalisasi Pelatihan Mandiri dan Komunitas Belajar serta penguatan supervisi kepala sekolah untuk meningkatkan inovasi pembelajaran secara berkelanjutan. Kata Kunci: inovasi guru; komunitas belajar; pelatihan mandiri; Platform Merdeka Mengajar; SMP